2021
DOI: 10.1093/mnras/stab1928
|View full text |Cite
|
Sign up to set email alerts
|

The MAVERIC Survey: Simultaneous Chandra and VLA observations of the transitional millisecond pulsar candidate NGC 6652B

Abstract: Transitional millisecond pulsars are millisecond pulsars that switch between a rotation-powered millisecond pulsar state and an accretion-powered X-ray binary state, and are thought to be an evolutionary stage between neutron star low-mass X-ray binaries and millisecond pulsars. So far, only three confirmed systems have been identified in addition to a handful of candidates. We present the results of a multi-wavelength study of the low-mass X-ray binary NGC 6652B in the globular cluster NGC 6652, including sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…We found a total of 87 unidentified X-ray sources with 𝐿 𝑋 > 10 32 erg s −1 in 29 GCs, while we did not find any unidentified sources with 𝐿 𝑋 > 10 33 erg s −1 in those GCs. However, we note a special case, the X-ray source B in NGC 6652 (see Heinke et al 2001;Stacey et al 2012), which is suggested as a transitional MSP (tMSP) in a recent work by Paduano et al (2021). It is considered to be in an accretion-powered state currently, with an average X-ray luminosity of ∼ 1.8 × 10 34 erg s −1 .…”
Section: Discussionmentioning
confidence: 86%
“…We found a total of 87 unidentified X-ray sources with 𝐿 𝑋 > 10 32 erg s −1 in 29 GCs, while we did not find any unidentified sources with 𝐿 𝑋 > 10 33 erg s −1 in those GCs. However, we note a special case, the X-ray source B in NGC 6652 (see Heinke et al 2001;Stacey et al 2012), which is suggested as a transitional MSP (tMSP) in a recent work by Paduano et al (2021). It is considered to be in an accretion-powered state currently, with an average X-ray luminosity of ∼ 1.8 × 10 34 erg s −1 .…”
Section: Discussionmentioning
confidence: 86%
“…Despite the limited statistical signal in many of the sample clusters, our ATCA survey has already been successful in identifying new compact binaries in globular clusters, such as the ultracompact black hole X-ray binary candidate X9 in 47 Tuc (Miller-Jones et al 2015;Bahramian et al 2017) and the transitional millisecond pulsar candidate NGC6652B (Paduano et al 2021). This highlights the need and opportunity for detailed follow-up of each central radio source in our catalogue-many are likely to be true cluster sources, even if the individual cluster does not formally show a statistical excess of sources.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from pulsars, we have also detected some well-known X-ray binaries-in Terzan 5, EXO 1745-248, which was in outburst at the time of the observations (Tetarenko et al 2016b), here catalogued as Ter5-ATCA3; in NGC 6624, 4U 1820-30, here catalogued as N6624-ATCA1 (see Russell et al 2021 andPanurach et al 2021); and in Terzan 6, GRS 1747-312, here catalogued as Ter6-ATCA1 (see Panurach et al 2021). We have previously published two X-ray binaries discovered as part of this ATCA survey: in 47 Tuc, the candidate black hole X9 (Miller-Jones et al 2015), here catalogued as 47Tuc-ATCA1; and in NGC 6652, the candidate transitional millisecond pulsar NGC6652B (Heinke et al 2001;Paduano et al 2021), here catalogued as N6652-ATCA3.…”
Section: Known Sourcesmentioning
confidence: 97%
“…This overabundance is due to the formation channels of XRBs There are currently three confirmed tMSPs and a handful of other candidates, of which one confirmed tMSP resides within the GC M28 (Papitto et al 2013). Two candidate tMSPs also reside within the clusters Terzan 5 and NGC 6652 respectively (Bahramian et al 2018b;Paduano et al 2021). Cataclysmic variables (CVs), white dwarfs accreting from low mass stars, make up a large fraction of X-ray emitting binaries in globular clusters (Grindlay et al 2001;Pooley et al 2002).…”
Section: X-ray Binaries In Globular Clustersmentioning
confidence: 99%
“…Further details about the observations of the cluster sample and the reduction of the radio data are presented in Tremou et al (2018) and Shishkovsky et al (2020). In addition to the identification of several BH candidates in Galactic GCs (see 1.1), the MAVERIC survey has also identified tMSP candidates (Bahramian et al 2018b;Paduano et al 2021), and placed limits on the existence of intermediate mass BHs in GCs (Tremou et al 2018). Accompanying the MAVERIC survey is a catalogue of over 1100 X-ray sources detected by the Chandra X-ray Observatory's ACIS detector from observations of 38 GCs (Bahramian et al 2020).…”
Section: The Maveric Surveymentioning
confidence: 99%